Cognitive Versus Hemorrhagic Onset in Cerebral Amyloid Angiopathy: Neuroimaging Features - Perini, Giulia; Ramusino, Matteo C.; Farina, Lisa Maria; Fabbro, Beatrice Dal; Canavero, Isabella; Picascia, Marta; Muzic, Shaun; Ballante, Elena; Cavallini, Anna; Pichiecchio, Anna; Costa, Alfredo (Current Alzheimer Research, 2023)
Background: Intracerebral hemorrhage and cognitive decline are typical clinical presentations of cerebral amyloid angiopathy (CAA). Objective: To determine whether magnetic resonance imaging (MRI) features differ between CAA with hemorrhagic versus cognitive onset. Methods: In this retrospective study, sixty-one patients with CAA were classified by onset presentation of the disease: hemorrhage (n = 31) or cognitive decline (n = 30). The two groups were compared for MRI markers of small vessel disease, namely cerebral microbleeds (CMBs), cortical superficial siderosis, white matter hyperintensities (WMHs), enlarged perivascular spaces, cortical microinfarcts, and visual rating scales for cortical atrophy. In the patients with cognitive onset, further exploratory analyses investigated MRI markers according to cerebrospinal fluid (CSF) and neuropsychological profiles. Results: Patients with cognitive onset showed a higher prevalence of CMBs (p < 0.001), particularly in temporal (p = 0.015) and insular (p = 0.002) lobes, and a higher prevalence of WMHs (p = 0.012). Within the cognitive onset group, 12 out of 16 (75%) patients had an Alzheimer’s disease (AD) CSF profile but did not differ in MRI markers from those without AD pathology. Patients with cognitive onset displayed a multidomain profile in 16 out of 23 (70%) cases; patients with this profile showed increased WMHs and CMBs in parietal lobes compared with the amnestic group (p = 0.002) and dysexecutive group (p = 0.032), respectively. Conclusion: Higher burdens of WMHs and CMBs, especially in temporal and insular lobes, are associated with the cognitive onset of CAA. MRI markers could help to shed light on the clinical heterogeneity of the CAA spectrum and its underlying mechanisms.
Keywords: clinical presentation